2019
DOI: 10.1088/1748-9326/ab4032
|View full text |Cite
|
Sign up to set email alerts
|

Trends in PM2.5 transition metals in urban areas across the United States

Abstract: Using data from the Environmental Protection Agency's Chemical Speciation Network, we have characterized trends in PM 2.5 transition metals in urban areas across the United States for the period 2001-2016. The metals included in this analysis-Cr, Cu, Fe, Mn, Ni, V, and Zn-were selected based upon their abundance in PM 2.5 , known sources, and links to toxicity. Ten cities were included to provide broad geographic coverage, diverse source influences, and climatology: Atlanta (ATL), Baltimore (BAL), Chicago (CHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“… 19 , 30 The ambient levels of tracers of industrial emissions (Cr, Cu, Fe, and Mn) and crude oil (Ni, V) combustion also declined during the same period. 19 , 31 Slightly higher declining rates were computed for heavily populated urban sites in NYC and NJ as compared to those computed for peri-urban sites. A less pronounced decline has been also observed in the Upstate New York region farther away from the major urban centers with reduction rates of 3 to 4 µg/m 3 /year.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 , 30 The ambient levels of tracers of industrial emissions (Cr, Cu, Fe, and Mn) and crude oil (Ni, V) combustion also declined during the same period. 19 , 31 Slightly higher declining rates were computed for heavily populated urban sites in NYC and NJ as compared to those computed for peri-urban sites. A less pronounced decline has been also observed in the Upstate New York region farther away from the major urban centers with reduction rates of 3 to 4 µg/m 3 /year.…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously shown that wildfires smoke concentrations were strongly related the frequency and magnitude of wildfires in eastern US. 13 - 36 In this analysis, industrial and residential wood combustion were included in the industrial sector emissions. According to the 2014 NEI, 14 000 metric tons of PM 2.5 (one-third of industrial emissions) were emitted from biomass burning accounting for approximately 93% of residential wood combustion.…”
Section: Resultsmentioning
confidence: 99%
“…For the precipitation experiments, SRM-1648a extract was added to the DTT assay at three concentration levels (Table 1), which were selected according to the range of Fe concentrations measured in ten urban areas across the US using accepted PM lter sampling and extraction protocols. 36,49,50 The concentrations of the remaining elements were calculated based on the dilution factor (DF) and the elements' concentration in the SRM-1648a extract. Note that the Cu concentration for samples 1, 2, and 3 and Mn concentration for samples 1 and 2 were below the DL for the colorimetric analysis.…”
Section: Metal Precipitation Of Urban Pm (Srm-1648a) In the Dtt Assaymentioning
confidence: 99%
“…Note that the Cu concentration for samples 1, 2, and 3 and Mn concentration for samples 1 and 2 were below the DL for the colorimetric analysis. To maintain the relevance of Mn and Cu concentrations to that in PM lter extracts (0.058 mM Mn and 0.06 mM Cu), 36,49,50 increasing the SRM-1648a sample concentrations above the DL for Mn and Cu was not preferred. Also presented in Table 1 are metal solubilities and saturation indexes (SI) determined by MINEQL 36,81 under the DTT assay conditions (0.1 M TOTPO 4 , T ¼ 37 C, pH ¼ 7.4 and ionic strength ¼ 0.22 M).…”
Section: Metal Precipitation Of Urban Pm (Srm-1648a) In the Dtt Assaymentioning
confidence: 99%
See 1 more Smart Citation